CaF2 nanoparticles deliver siRNA targeting STAT6 and PPAR- γ to depolarise tumour-associated macrophages - Hamed Al-Busaidi; Won Fen Wong; Lakshmi Selvaratnam; Ezharul Hoque Chowdhury (BBA Advances)
Breast cancer is a leading cause of death in women, partly due to challenges posed by constituents of the tumour-microenvironment, such as tumour-associated macrophages (TAMs). Polarisation of macrophages to a pro-tumour phenotype usually involves STAT6 and PPAR- γ pathways. In this study, CaF2 nanoparticles were developed and bound to siRNA to inhibit the expression of STAT6 and PPAR-γ in an in vitro model of TAMs. CaF2 nanoparticles were synthesised by precipitation reactions and characterised by spectrophotometry, dynamic light scattering, FTIR, electron microscopy and MTT assay. Their binding affinity to siRNA was confirmed, as was the cellular uptake by TAMs. CaF2-bound siRNAs targeting STAT6 and PPAR-γ were found to reduce the expression of M2 phenotype when assessed by PCR and microscopy. These findings open the possibility of using nanoparticle-bound siRNA to target genes associated with pro-tumour polarisation in macrophages, with further potential to repolarise them to a more inflammatory phenotype.